Serum Adiponectin and Vaspin Levels in Systemic Sclerosis - Ozgen, Metin; Koca, Suleyman Serdar; Isik, Bahar; Gundogdu, Baris; Ustundag, Bilal; Isik, Ahmet (Walter de Gruyter Gmbh, 2011)
Objective: Chronic inflammatory disorders such as rheumatoid arthritis and systemic lupus erythematosus (SLE), which are associated with insulin resistance and accelerated atherosclerosis, also lead to increased adipokines levels. However, it is not fully known whether systemic sclerosis (SSc), another chronic inflammatory disease, leads to insulin resistance and atherosclerosis and affects adipokine levels. Thus, the aim of the present study was to determine the serum adiponectin and vaspin levels and their possible effects on the homeostasis model assessment for insulin resistance (HOMA-IR) index and intima-media thickness (IMT) of the common carotid artery in a cohort of patients with SSc Method: Twenty-three patients with SSc, 22 patients with SLE (serving as a patient control group), and 29 healthy controls (HCs) were included in this study. Serum adiponectin and vaspin levels and the HOMA-IR index and IMT were determined. Results: Adiponectin level was significantly lower in the SSc group than in the SLE or HC groups and the decrease of vaspin level was significant after adjusting for age in the SSc group compared to the SLE group. HOMA-IR indexes were similar in the SSc and HC groups, but higher in the SLE group. IMTs were higher in both patient groups than in the HC group. Adiponectin and vaspin serum levels were not correlated with either HOMA-IR index or IMT in SSc. Conclusion: SSc is associated with decreased adipokines levels, but does not induce insulin resistance, in contrast to SLE. Similar to SLE, SSc accelerates atherogenesis. Further studies are needed to elucidate the role of adipokines in SSc.
Sistemik sklerozda serum adiponektin ve vaspin düzeyleri
Keywords: Systemic sclerosis; systemic lupus erythematosus; adiponectin; vaspin; insulin resistance